1996
DOI: 10.1002/(sici)1096-9926(199603)53:3<158::aid-tera3>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of retinoid-induced teratogenic effects: Possible relationship with relative selectivity for nuclear retinoid receptors RARα, RARβ, and RARγ

Abstract: Retinoic acid, an oxidative metabolite of vitamin A, is involved in the control of many biological processes including embryonic development. Excess as well as deficiency of retinoids were found to be teratogenic. The effects of retinoids in normal as well as abnormal development may be mediated by two members of retinoid receptors, the RAR's and RXR's, which exhibit a specific temporal and spatial expression during development. The significance of the retinoid receptors was investigated here by studying the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 44 publications
1
15
0
Order By: Relevance
“…First, it has been shown that synthetic retinoids that are unable to activate RARs are non-teratogenic (Kochhar et al, 1996), whereas RAR isotype-selective retinoids produce a distinct spectrum of defects (Elmazar et al, 1996;Arafa et al, 2000). Second, overexpression of RARγ in Xenopus embryos potentiates the RA-induced loss of cranial structures, whereas expression of a dominant-negative form of RARs results in a resistance to RAinduced malformations (Old et al, 1996;Blumberg et al, 1997;van der Wees et al, 1998).…”
Section: Fig 8 Expression Of Hoxa1mentioning
confidence: 99%
See 1 more Smart Citation
“…First, it has been shown that synthetic retinoids that are unable to activate RARs are non-teratogenic (Kochhar et al, 1996), whereas RAR isotype-selective retinoids produce a distinct spectrum of defects (Elmazar et al, 1996;Arafa et al, 2000). Second, overexpression of RARγ in Xenopus embryos potentiates the RA-induced loss of cranial structures, whereas expression of a dominant-negative form of RARs results in a resistance to RAinduced malformations (Old et al, 1996;Blumberg et al, 1997;van der Wees et al, 1998).…”
Section: Fig 8 Expression Of Hoxa1mentioning
confidence: 99%
“…Moreover, the ligand-bound RXR is transcriptionally active only if its RAR partner is also ligand-bound (the so-called RXR subordination) (Lotan et al, 1995;Roy et al, 1995;Horn et al, 1996;Taneja et al, 1996;Botling et al, 1997;Chiba et al, 1997;Minucci et al, 1997;Altucci and Gronemeyer, 2001). Along the same lines, RXR-selective ligands, which are inactive on their own, synergize in vivo with RARα-and RARγ-selective ligands to generate congenital malformations (Kochhar et al, 1996;Lu et al, 1997;Elmazar et al, 1996;Elmazar et al, 1997;Elmazar et al, 2001). In our experiments, the panRXR agonist BMS649 (SR11237) had no effect on its own, indicating that neither RXR homodimers, nor other heterodimers in which the RXR partner is transcriptionally active on its own, mediate the teratogenic effects of retinoids on the branchial region.…”
Section: Rarβ/rxr Heterodimers Mediate Teratogenic Effects Of Ra In Tmentioning
confidence: 99%
“…We demonstrated astRA (at dose 25 mg/kg, IP) decreased number of renal corpuscles and increased periglomerular space and diameter of renal corpuscles. Elmazar et al (1996) found hypoplasia of kidney, hydronephrosis and hydroureter after administration of RA (37.5 mg/kg body weight). In the present study we focused on the effects of RA on histological structure of fetal kidney.…”
Section: Discussionmentioning
confidence: 99%
“…RARα ligands cause deformities of the ear, mandible and limb, RARβ ligands cause defects of the urinary system and liver, and RARγ ligands cause ossification deficiencies and defects of the sternebrae and vertebral body. [33][34][35] Excess intake of retinoids can cause deleterious effects not only in wild animals but also in humans.…”
Section: Biological Effects By Excess Rar Signalingmentioning
confidence: 99%